The effects of Juniperus oxycedrus ssp oxycedrus essential oil on memory, anxiety and depression in amnesic rats - Akbaba, Emel; Othman, Safeen Ahmed; Bağcı, Eyüp (My University, 2017)
In the present study, memory-enhancing, anxiolytic and antidepressant-like activities of Juniperus oxycedrus ssp oxycedrus (Cupressaceae) essential oil on scopolamine-induced amnesic rats are assessed. Scopolamine is a drug comprising highly amnesic properties; therefore it has been used to create dementia animal model. Scopolamine is known to induce memory impairment as well as anxiety and depressive-like behavior in animals and humans. In this study, we evaluated the neuroprotective effects of Juniperus oxycedrus ssp oxycedrus essential oil in scopolamine treated rats. Two different doses, 1% and 3%, of essential oil were administrated to the rats by inhalation for 21 continuous days prior to the behavioral analysis. Y-maze task and radial arm maze task were used to evaluate spatial memory performances of the rats. As expected, scopolamine treated rats exhibited the following: decreases in spontaneous alternation percentage in Y-maze task, and increases in working memory errors and reference memory errors in radial arm maze task. Juniperus oxycedrus ssp oxycedrus essential oil treated rats exposed to scopolamine showed significant improvement in spatial memory function as compared to scopolamine-alone treated rats. Furthermore, anxiety and depressive like symptoms were assessed by elevated plus maze task and forced swimming task. Juniperus oxycedrus ssp oxycedrus essential oil inhalation significantly increased the number of open arm entries in elevated plus maze, indicating anxiolytic behavior. The essential oil also reduced the immobility time and increased the swimming time in forced swimming test indicating antidepressant activity. Taken together, Juniperus oxycedrus ssp oxycedrus essential oil could be a good candidate for the treatment of dementia and deserves further investigation
Bildiri - Yayımlanmış
Keywords: Juniperus oxycedrus ssp oxycedrus essential oil; Memory; Dementia; Anxiety; Depression